2009
DOI: 10.1016/j.yexmp.2009.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Combined yeast-derived β-glucan with anti-tumor monoclonal antibody for cancer immunotherapy

Abstract: β-Glucan is an immuno-stimulating agent that has been used to treat cancer and infectious disease for many years with varying and unpredictable efficacy. Recent studies have unraveled the action mode of yeast-derived β-glucan in combination with anti-tumor monoclonal antibodies (mAbs) in cancer therapy. It has demonstrated that particulate or large molecular weight soluble β-glucans are ingested and processed by macrophages. These macrophages secrete the active moiety that primes neutrophil complement receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 65 publications
2
48
0
1
Order By: Relevance
“…We recently found that high molecular weight, unbranched (1 3),(1 4)-β -glucan from barley suppresses growth of PDT-treated Lewis lung carcinoma tumors (Akramiene et al 2009), but others reported that also schizophyllan, a branched high molecular weight (1 3),(1 6)-β -glucan, potentiates PDT (Krosl and Korbelik 1994). These studies agree with recent observations that apart from the presence of the (1 3),(1 6)-β linkage, the size and complexity of β -glucan are important for the interaction with human cells (Liu et al 2009). Therefore, β -glucan from different sources may affect tumor growth differently.…”
supporting
confidence: 87%
See 2 more Smart Citations
“…We recently found that high molecular weight, unbranched (1 3),(1 4)-β -glucan from barley suppresses growth of PDT-treated Lewis lung carcinoma tumors (Akramiene et al 2009), but others reported that also schizophyllan, a branched high molecular weight (1 3),(1 6)-β -glucan, potentiates PDT (Krosl and Korbelik 1994). These studies agree with recent observations that apart from the presence of the (1 3),(1 6)-β linkage, the size and complexity of β -glucan are important for the interaction with human cells (Liu et al 2009). Therefore, β -glucan from different sources may affect tumor growth differently.…”
supporting
confidence: 87%
“…Without β -glucan, iC3b-opsonized tumor cells are resistant to killing, because they, like all human and mammalian cells, lack β -glucan in their membrane. Microbes can activate the lectin domain on CR3, leading to effective phagocytosis and cytotoxic degranulation (Cheung and Modak 2002;Gelderman et al 2004;Liu et al 2009). Therefore, these processes can be induced by coadministration of β -glucan together with the agents, which cause opsonization of tumor cells by iC3b fragment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Furthermore, it has been recently reported b-glucans enhance Ag-specific T cells and B cells responses by promoting the maturation and antigen presentation of DCs. 12,[16][17][18]31 Thus, b-glucans play a key role in the innate and adaptive immune responses.…”
Section: Administration Of Sinfia Into Tumor Tissue Delays Tumor Progmentioning
confidence: 99%
“…In recent years, there has been increasing biotechnological and commercial interest in yeast cell wall components, including their use as biological response modifiers, anti-cancer agents, bioadsorbents, ingredients in food processing and cosmetic formulations, and as systems for immobilizing oral vaccines, antibodies and enzymes of industrial significance 6,25,33 . This increase in interest has occurred concomitantly with our better understanding of the chemical composition, genetic regulation and functional properties of cell wall components.…”
Section: Fraction Weight (Mg) (1→4)-α-d-glucan (% W/w) (1→6)-β-d-glucmentioning
confidence: 99%